A rare case of primary tuberculosis infection with concurrent pleomorphic adenoma of the parotid gland - Hassan Mohamed Al Bisher (MDPI AG, 2010)
Coexistence of parotid tuberculosis along with a benign parotid tumor is a rare entity with only nine cases reported in the literature. We report here a case of primary parotid tuberculosis with concurrent pleomorphic adenoma in a 51-year-old female.